(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease that reduces hand grip strength, affecting daily functions. The Jamar Hydraulic Hand Grip Dynamometer is commonly used to assess grip strength in RA patients, but factors like joint deformities and pain may influence measurement accuracy. This review examines its use in evaluating RA patients. Methods: The review of this studies from PubMed, Google Scholar, and Scopus was conducted, focusing on RA patients who underwent grip strength testing with the Jamar dynamometer. Studies were assessed for design, sample size, patient demographics, and outcomes related to grip strength, disease severity, and functional impairment. Results: Studies show that RA patients have significantly reduced grip strength, correlating with disease activity and disability. The Jamar dynamometer is reliable and valid, providing consistent results, though pain and joint deformities can affect measurements. Conclusion: The Jamar Hydraulic Hand Grip Dynamometer is an effective tool for assessing grip strength in RA patients. It helps monitor disease progression and treatment effectiveness, though future research should focus on standardizing protocols and addressing measurement variability.